3.30. Podaj miejsca zerowe funkcji: a) y = (x + 2)(x – 7) d) y y = (x – 8)(x * sqrt(3) + sqrt(6)) b) e) y = 3(2x – 8) * x; y = (2 – 2x)(x – 3) c) f) c) f(x) = 3 * (x – 7) ^ 2 – 27; f(x) = – 2 – 2x ^ 2; y = – 4 * (x + 5) ^ 2; y = 3 * (4 – x + sqrt(2)) ^ 2

3.30. Podaj miejsca zerowe funkcji: a) y = (x + 2)(x – 7) d) y y = (x – 8)(x * sqrt(3) + sqrt(6)) b) e) y = 3(2x – 8) * x; y = (2 – 2x)(x – 3) c) f) c) f(x) = 3 * (x – 7) ^ 2 – 27; f(x) = – 2 – 2x ^ 2; y = – 4 * (x + 5) ^ 2; y = 3 * (4 – x + sqrt(2)) ^ 2